Identifying Average Reservoir Pressure in Multilayered Oil Wells Using Selective Inflow Performance (SIP) Method - Tarq, Shamam; Al-Obaidi , Dahlia A. (Iraqi Journal of Chemical and Petroleum Engineering, 2023)
The downhole flow profiles of the wells with single production tubes and mixed flow from more than one layer can be complicated, making it challenging to obtain the average pressure of each layer independently.  Production log data can be used to monitor the impacts of pressure depletion over time and to determine average pressure with the use of Selective Inflow Performance (SIP). The SIP technique provides a method of determining the steady state of inflow relationship for each individual layer. The well flows at different stabilized surface rates, and for each rate, a production log is run throughout the producing interval to record both downhole flow rates and flowing pressure. PVT data can be used to convert measured in-situ rates to surface conditions. Different types of Inflow Performance Relationship (IPR) equations can be used for SIP interpretation, including the Straight-line method, Fetkovitch method, and Laminar Internal Turbulent (LIT) relations. Although the SIP method can be used for single-phase flow, the interpreter can restrict the IPR’s calculations to a particular phase. This research discusses the difficulties in estimating the average reservoir pressure in multilayered reservoir completed wells over their production life. The SIP technique has been applied to some producing wells in the south of Iraq, which are completed in multiple producing reservoirs previously tested with a formation tester to estimate reservoir pressure and other parameters. Two wells are taken in the south of Iraq region, Zubair Oil Field, one with cross flow between perforations and the other well with no cross flow. An average pressure is not calculated for layer A in Well-1, because there is no contribution rate. While the average pressure for Well-1, layer B is 3414.49 psia. Also, the average pressure for Well-2, layer H is not calculated because there is no rate contribution from this layer, and the maximum average pressure was calculated in layer G, which is about 2606.26 psia. It is also found that the presence of cross flow has no effect on SIP calculations.